Analisis Wacana pada Kumpulan Lirik Lagu Iwan fals dengan Menggunakan Teori Kohesi Leksikal - Marlina Tambunan (Medan Resource Center, 2022)
This study aims to describe cohesion, especially lexical cohesion contained in a collection of songs created by Iwan Fals. The method used is descriptive method. The data sources used are the songs entitled “Office Rat”, “Ruble”, “Bachelor of Youth”, “Voice of the People's Representatives”, “Half-God Man”. The results of the lexical cohesion research in the collection of Iwan Fals songs are 38 repetition data, 11 collocation data, and 11 synonym data. In this case, repetition dominates the lexical cohesion contained in the collection of Iwan Fals songs. The use of lexical cohesion is to get cohesion through the choice of vocabulary, the intensity of the meaning of the language, and the beauty of the language. Thus, the discourse of the song will be more varied and create a discourse linkage and bind the relationship between elements in the sentence. Keywords: Discourse; Lexical Cohesion; Song